Knowledge and Practice Assessment In The Implementation of Malaria Primary Prevention in The Azire Health Area in Northwest Cameroon - Oliver Fon, Taah; Emmanuel Fonyuy, Bodzewan; Fon Elvis, Tata (International Research in Medical and Health Sciences, 2019)
In 2013, worldwide, there were an estimated 198 million cases of malaria. Most of these cases were in the WHO African Region (82%) followed by the Southeast Asian Region (12%) and the Eastern Mediterranean Region ( 5%). About 8% estimated cases globally are due to Plasmodium vivax, although, the proportion outside the African continent is 47%. The research aimed to assess the implementation of primary preventive measures against malaria in their infants by nursing mothers aged 15- 49 years attending IWC at the Azire IHC. A descriptive cross-section all study design to collect primary data on the knowledge and practice leading to exposures and outcomes associated with malaria infection in infancy, in a single contact with the respondents. Results show that61.5%, 27.7%, and 10.8% stated they kept clean environments, used mosquito nets and mosquito sprays respectively, to control mosquitoes. The practice of tucking the LLIN has averagely implemented: 54% of respondents tucked the LLINs every night in a week. 8% respondents either did not tuck the LLINs or tucked it once in 7 nights, 20% respondents tucked it 4 or 5 nights, and 54% respondents tucked the LLINs every night in a week. Generally, regarding knowledge of malaria; nursing mothers aged 15-49 years attending Infant Welfare Clinics at the Azire IHC had a fair knowledge of malaria because only 2 % respondents stated malaria was caused by the Plasmodium parasite,14.3% respondents stated malaria was transmitted by unhygienic conditions and 6.4% stated headache was observable on infants.